Out-of-hospital cardiac arrest - Martin Porzer (Biomedical Papers, 2017)
Out-of-hospital cardiac arrest (OHCA) is a leading cause of death in developed industrial countries. The global worldwide average of OHCA incidence in adults is 95.9/100,000/year. European incidences vary according to source from 16 to 119/100,000/year. The aim of this study was to provide an overview of current information on OHCA. The incidences in various populations are discussed, along with the factors affecting the prognosis and outcome of these patients. The etiology and pathophysiological mechanisms are also described, especially in relation to the most common causes - acute and chronic forms of coronary artery disease and cardiomyopathies. Measures that could improve survival rates are discussed, with emphasis on the role of the general public and deployment of automatic external defibrillators.